Kepala Sekolah Sebagai Manajer (Kompetensi Manajerial), Kepala Sekolah Sebagai Supervisior - Qulbi, Amar (Jurnal Ilmiah Wahana Pendidikan, 2025)
The aim of this research is to determine the role of managerial competence and supervision of school principals at MTs Al-wasli'ah. This research uses a qualitative approach with a descriptive-analysis model. In other words, the main sources in this research are books, articles and other reading sources related to school principals as managers and supervisors and also researchers conducting interviews for analysis related to leadership style. In this research, the resource person chosen was the principal of MTs Al-Wasliyah. This analysis analyzes the managerial and supervisory competencies of the head of MTs Al-Wasliyah. In this research, researchers found that the implementation of managerial and supervisory competencies was not optimal and evenly distributed, so more thorough evaluation and improvement was needed.